IMMUNOHISTOCHEMICAL ANALYSIS OF SFLT-1 AND ADAMTS-8 EXPRESSION IN DIABETIC RAT TESTIS TISSUE - Seval Kaya (Rojan GÜMÜŞ, 2019)
he aim of this study was to determine the testicular inflammation and angiogenetic effect of diabetes with ADAMTS-8 and SFlt-1 proteins immunohistochemically. Wistar albino male rats (n: 12)were used for the study, Group 1: Control group (n: 6), only 1 ml i.p. saline injection was performed. Group 2: Diabetes group (n: 6) received a single intraperitoneal dose of streptozotocin (STZ) of 60 mg / kg. The glucose value measured above 250 mg / dl was considered as diabetic. Under anesthesia, dissection was performed at the lower part of abdominal clearance and testicular tissue was removed. Testis tissues were fixed in 10% neutral formalin, followed by the routine paraffin protocol and cut with a microtome. Then, primary antibodies (ADAMTS-8, sFlt-1) were applied by immunohistochemistry method and incubated at +4 ˚C overnight. The sections were then examined under a light microscope. Diabetes group showed that Leydig cells in the inter tubular area had vacuolization and capillary dilatations in histopathological examinations. sFlt-1 staining of control group showed positive expression in capillary endothelium between Leydig chambers of the intertubular area. Sflt-1 expression of diabetes group was observed in degenerative spermatic cells and Sertoli cells of the basement membrane facing tubules. The expression of ADAMTS-8in control group was positive in some Leydig cells in the interstitial area of Sertoli cells in seminiferous tubule but, spermatogenetic cells were negative. In the ADAMTS-8 staining of diabetes group, the expression of ADAMTS-8 was increased in the stromal cells and some inflammatory cells in the intertubular space. SFlt-1 plays a crucial role in angiogenesis as well as in diabetic testes and is marked as a precursor for the disruption of vascular structure and blood flow due to degenerative changes. It is thought that the distribution of ADAMTS-8 may be a determinant protein in the development of extracellular matrix and in damage to testicular tissue of diabetic testis.